Influence of Er,Cr:YSGG Laser Irradiation on the Push-Out Bond Strength of Zirconia and Glass Fiber Posts with Radicular Dentin - Alofi, Raneem S.; Alshiddi, Ibraheem F.; AlFawaz, Yasser F.; Alsahhaf, Abdulaziz; Al-Aali, Khulud Abdulrahman; Abduljabbar, Tariq; Vohra, Fahim (International Journal of Biomaterials, 2019)
Objective. This in vitro study was designed to evaluate the influence of an Er,Cr:YSGG laser on the bond strength of zirconia and glass fiber posts with root dentin. Materials and methods. Ninety extracted single-rooted human teeth were randomized into 6 groups (n = 15/group) on the basis of different posts (zirconia/glass fiber) and Er,Cr:YSGG laser tips (axial and radial). Specimens were prepared for push-out testing with the help of a cutting machine; six slices (2 on each cervical, middle, and apical) of approximately 1 mm thickness were sectioned for all roots on a plane perpendicular to the long axis of the post. All specimens were placed into a universal testing machine with a defined 0.5 mm/min crosshead speed until the maximum failure load was obtained. Results. The highest mean push-out bond strength of the glass fiber and zirconia groups was achieved with laser treatment. The highest push-out bond strength was achieved with the axial fiber tip (7.63 ± 1.22 MPa), and the lowest was achieved with a radial fiber tip of the glass fiber group (6.98 ± 0.96 MPa). ANOVA showed a statistically significant difference between the groups (p=0.041). The mean push-out bond strength was found to be higher with an axial fiber tip for both cervical and apical segments in the glass fiber and zirconia groups (p<0.05). The independent t-test resulted in the overall highest mean push-out bond strength in the apical segments (p=0.026). Conclusion. Within the limits of the present in vitro research study, an enhancement in the push-out bond strength of resin cement, mainly in the cervical region of the root canal, was achieved after irradiation with an Er,Cr:YSGG laser using an axial fiber tip.